Full of sound and fury, but signifying something: XVI International AIDS Conference, Toronto, Canada, August 13-18, 2006 - Wells, William A. (The Rockefeller University Press, 2006)
The biennial AIDS conference is often exhausting and irritating, but it offers a unique view of how science and society interact. It still deserves the support of basic scientists.